Engineering of the zinc-binding domain of an esterase from Clostridium botulinum towards increased activity on polyesters. Issue 6 (13th March 2017) - Biundo, Antonino; Steinkellner, Georg; Gruber, Karl; Spreitzhofer, Theresa; Ribitsch, Doris; Guebitz, Georg M.
Abstract : Variants of the zinc-binding domain of Clostridium botulinum EstA (Cbotu_EstA) release more building blocks (Ta and BTa) from the aromatic/aliphatic copolyester poly(butylene adipate- co -terephthalate) (PBAT). Abstract : The carboxylesterase from Clostridium botulinum (Cbotu_EstA) has been shown to hydrolyze the surface of the polyester poly(butylene adipate- co -terephthalate) (PBAT) releasing the monomeric building blocks. Cbotu_EstA contains a zinc ion, tetrahedrally coordinated by two histidine and two aspartic acid residues, which is buried inside an extra domain typical for members of the I.5 lipase family. To elucidate the role of this extra domain with regard to polyester hydrolysis, variants of the zinc-binding domain were constructed and expressed in E. coli BL21-Gold(DE3). These enzyme variants were characterized with respect to their specific activity, kinetic parameters and thermostability on soluble substrates as well as on PBAT. All the variants exhibited a similar affinity towards the small substrate para -nitrophenyl butyrate ( p NPB), with K M values between 0.4 and 1.2 mM, while the catalytic efficiency decreased approximately 1000-fold for the zinc-binding variants and 5-fold for the zinc cavity variants. Moreover, all four variants of the zinc-coordination site (D130L, H150F, H156F, and D302L) showed a loss of thermostability. However, H156F and D302L revealed a drastic loss of thermostability compared to D130L and H150F. Nevertheless, compared to Cbotu_EstA, variants carrying substitutions of amino acids in the zinc-binding domain were able to release up to 10 times more soluble products from the polymeric substrate PBAT. The thermostability at 50 °C was increased in the case of F154Y and W274H, carrying more hydrophilic residues. These data clearly demonstrate the importance of different regions of the zinc-binding domain for the hydrolysis of polyesters like PBAT.